2015
DOI: 10.1142/s0219749915500446
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of entanglement and non-classical correlation for four-qubit GHZ state

Abstract: Many-qubit entanglement is crucial for quantum information processing although its exploitation is hindered by the detrimental effects of the environment surrounding the many-qubit system. It is thus of importance to study the dynamics of general multipartite nonclassical correlation, including but not restricted to entanglement, under noise. We did this study for four-qubit GHZ state under most common noises in an experiment and found that nonclassical correlation is more robust than entanglement except when … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In fact, until the present, the quantification and characterization of the exact amount of entanglement between the different constituent parts of a multi-partite entangled quantum system remains a challenging task and has been calculated only for particular model of decoherence and particular quantum states [39]. Nevertheless, many different entanglement measures for multi-partite entangled quantum systems defined as the sum of the bipartite entanglement measures over all the possible bi-partitions of total quantum system have been proposed during the years [40,41] (see also the review papers [42,43] and the references therein) and some interesting results based on this strategy have been obtained [44][45][46][47][48][49][50][51][52][53][54][55]. For instance, it has been found that for multi-qubit systems, the degree of entanglement robustness tends to increases or decreases with the increase of the number of qubits of the system [8,56].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, until the present, the quantification and characterization of the exact amount of entanglement between the different constituent parts of a multi-partite entangled quantum system remains a challenging task and has been calculated only for particular model of decoherence and particular quantum states [39]. Nevertheless, many different entanglement measures for multi-partite entangled quantum systems defined as the sum of the bipartite entanglement measures over all the possible bi-partitions of total quantum system have been proposed during the years [40,41] (see also the review papers [42,43] and the references therein) and some interesting results based on this strategy have been obtained [44][45][46][47][48][49][50][51][52][53][54][55]. For instance, it has been found that for multi-qubit systems, the degree of entanglement robustness tends to increases or decreases with the increase of the number of qubits of the system [8,56].…”
Section: Introductionmentioning
confidence: 99%
“…The degradation level observed in four independent environments is far higher than that observed in three independent environments under the same noise [45]. The entanglement and coherence in the current dynamical map survive longer than that observed in four qubit GHZ-class states under classical detrimental noises, resulting in a rapid monotonic decay [66]. However, when compared to the entanglement preservation obtained under dynamics noise for a four-qubit GHZ-like state, as discussed in [60], the current one seems short-lived.…”
Section: Time Evolution Of Four Qubit Ghz State In Ise Interactionmentioning
confidence: 68%
“…For this case, the Lindblad equation is solved for the Pauli channels σ x , σ y , σ z as well as the isotropic channel and the lower bound ( 12) is computed for each case in Ref. [32]. Here, we only present the results as follows:…”
Section: Evolution Of Entanglement Of Maximal Entangled Four-qubit St...mentioning
confidence: 99%